2016
DOI: 10.1159/000449501
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Models: A Guide to Understand and Mitigate Aging?

Abstract: Aging is studied either on a systemic level using life span and health span of animal models, or on the cellular level using replicative life span of yeast or mammalian cells. While useful in identifying general and conserved pathways of aging, both approaches provide only limited information about cell-type specific causes and mechanisms of aging. Stem cells are the regenerative units of multicellular life, and stem cell aging might be a major cause for organismal aging. Using the examples of hematopoietic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The decline in the regenerative potential of tissues is one of the most obvious characteristics of aging, and stem cell exhaustion is widely accepted as a contributor to the decline in health during aging 30 . In accordance with this concept, aging phenotypes have been described for stem cells of multiple tissues, including those of the hematopoietic system, intestine, muscle, brain, skin, and germline.…”
Section: Hallmarks For Molecular Understanding Of Aging Biologymentioning
confidence: 99%
“…The decline in the regenerative potential of tissues is one of the most obvious characteristics of aging, and stem cell exhaustion is widely accepted as a contributor to the decline in health during aging 30 . In accordance with this concept, aging phenotypes have been described for stem cells of multiple tissues, including those of the hematopoietic system, intestine, muscle, brain, skin, and germline.…”
Section: Hallmarks For Molecular Understanding Of Aging Biologymentioning
confidence: 99%
“…Indeed, the proteostasis machinery normally prevents the accumulation of aberrantly folded proteins thanks to the action of several chaperones and co‐chaperones that play a crucial role in the refolding of misfolded toxic proteins. In neurodegenerative disorders, the impairment in the clearance of misfolded proteins has been associated to the deterioration of protein quality control systems, such as the UPS and/or the ALP (Brunauer, Alavez, & Kennedy, ; Manecka et al, ; Vijayakumaran & Pountney, ). Thanks to previous research carried out on yeasts, it is known that damaged or aggregated proteins can accumulate in the mother cells contributing in a decrease in the cell lifespan.…”
Section: Molecular Alterations Occurring In Neurodegenerationmentioning
confidence: 99%
“…Pre-clinical studies on sexual infertility-related diseases have suggested new directions to consider for the treatment of infertility [15]. Studies using experimental models have revealed the power of stem cell therapy for treating infertility and verified these results [16]. We herein review the research progress concerning the application of stem cells for treating infertility.…”
Section: Introductionmentioning
confidence: 99%